Pentingnya Penimbangan Berat Badan Balita Setiap Bulan di Desa Bung Bak Jok Aceh Besar - Khaira Rizki; Nurul Amna; Ellyza Fazlylawati (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
Toddler weight monitoring is a routine activity carried out by the integrated health post (posyandu). Routinely weighing toddlers means that toddler growth can be monitored intensively. The sooner it is found, the sooner cases of malnutrition or severe malnutrition will be handled. Data from the Ministry of Health shows that 65% of active integrated health posts in Indonesia have not reached the national target of 80%. The purpose of this activity is to optimize integrated health post activities. This community service activity has an influence on increasing mothers' knowledge of the importance of monthly weighing of toddlers.